Comparative transcriptomic analysis and identification of candidate genes related to Verticillium wilt resistance in Gossypium barbadense and Gossypium hirsutum - Jieyin Zhao; Xingui Hu; Yuxiang Wang; Jiaxin Lu; Wenju Gao; Xuening Su; Quanjia Chen; Yanying Qu (Plant Stress)
The resistance to Verticillium wilt in Gossypium barbadense is generally greater than that in Gossypium hirsutum, and analyzing the differences in the mechanism and regulatory genes involved in Verticillium wilt resistance between G. barbadense and G. hirsutum is particularly important. Here, we report a transcriptomic study for phenotypic evaluation of Verticillium wilt resistance in G. hirsutum (TM-1) and G. barbadense (Hai7124) and a comparison of the transcriptomes at 7 time points after Verticillium dahliae inoculation. Phenotypic evaluation revealed that, compared with TM-1, Hai7124 was more resistant to Verticillium wilt. A total of 18,138 differentially expressed genes (DEGs), including 1470 transcription factors (TFs). Further analysis of the expression of hormone biosynthesis- and signal transduction-related genes revealed that most of the genes in the salicylic acid (SA), jasmonic acid (JA) and ethylene (ET) biosynthesis pathways were highly expressed in Hai7124; the expression of SA and JA biosynthesis genes began to be significantly upregulated in the early stage of Verticillium wilt stress, while the expression of ET biosynthesis genes was upregulated mainly in the later stage. WGCNA-based binding sequence comparison revealed that MYB14 had nonsynonymous single nucleotide polymorphisms (SNPs) in 5 highly Verticillium wilt-resistant G. barbadense varieties compared to 5 highly Verticillium wilt-susceptible G. hirsutum varieties. Expression analysis revealed that GbMYB14 responded more rapidly to Verticillium wilt stress than the same gene in G. hirsutum. The resistance of G. barbadense and G. hirsutum to Verticillium wilt decreased after MYB14 silencing via virus induced gene silencing (VIGS), and leaf yellowing and necrosis in the GbMYB14-silenced plants were more obvious. Compared with those in G. hirsutum, the expression levels and of lignin biosynthesis pathway genes and the lignin content in GbMYB14-silenced plants were lower. In conclusion, our results provide a theoretical basis for an in-depth understanding of the molecular mechanism underlying the difference in Verticillium wilt resistance between G. barbadense and G. hirsutum and provide a new genetic resource for the study of cotton resistance to Verticillium wilt.